Rules of disengagement : the politics and honor of military dissent - Cohn, Marjorie, 1948- (PoliPoint Press ; Distributed by Ingram Publisher Services, 2009)
Rules of Disengagement examines the reasons men and women in the military have disobeyed orders and resisted the wars in Iraq and Afghanistan. It takes readers into the courtroom where sailors, soldiers, and Marines have argued that these wars are illegal under international law and unconstitutional under U.S. law. Through the voices of active duty service members and veterans, it explores the growing conviction among our troops that the wars are wrong. While the Obama Administration's pledge to remove all American troops from Iraq by the end of 2011 is encouraging - and in no small way likely.
Keywords: Selective conscientious objection -- United States.; Military ethics -- United States.; War -- Moral and ethical aspects -- United States.; Vietnam War, 1961-1975 -- Moral and ethical aspects.; Afghan War, 2001-2021 -- Moral and ethical aspects.; Iraq War, 2003-2011 -- Moral and ethical aspects.; Soldiers -- Legal status, laws, etc. -- United States.; POLITICAL SCIENCE -- General.; LAW -- General.; Ethics.; Military ethics.; Selective conscientious objection.; Soldiers -- Legal status, laws, etc.; War -- Moral and ethical aspects.; Iraq.; United States.; Soldat; Kampfeinsatz; Ethik; Militär; Kriegsdienstverweigerung; Militaires -- Statut juridique -- États-Unis.; Objection de conscience -- États-Unis.; USA.; Since 1961; Geschichte 1961-2008.; Electronic books.